IS METABOLOMICS THE DIAGNOSTIC TOOL FOR MEDICAL DIAGNOSTICS OF CANCER? AN EXAMPLE BASED ON LUNG AND BREAST CANCER - Lamasz, A.; Barg, W.; Mlynarz, P. (International Journal of Medicine and Medical Research, 2018)
Background. Metabolomics is a relatively new diagnostic tool that allows a deep insight into the body metabolism at a cellular level. Objective. This paper provides a comprehensive view into the metabolomic methodology and shows usefulness of this approach in diagnosing and stratifying lung and breast cancers. Methods. Literature review of metabolomics studies and its clinical application in the diagnosis of cancer-selected studies. Results. In general, the metabolomic approach comprises three steps: 1) sampling and preparing biofluids or tissue homogenates, 2) identification of low-molecular weight compounds up to 1.0 kDa using nuclear magnetic resonance, mostly 1H-NMR and/or mass spectrometry, and finally 3) data processing and analysing. It is possible to identify a set of metabolites which is specific for a certain metabolic status (the metabolic fingerprint). Furthermore, this set of metabolites provides information of possible pathomechanisms involved in the disease process i.e. information about the disease etiology. It has been proven that the change in metabolome precedes other biomarkers of the disease; not only clinical symptoms but other laboratory findings as well. Consequently, this approach, if sufficiently validated, seems to be very promising especially in screening and early diagnosing. Conclusions. It was demonstrated that metabolomic approach allows to discriminate patients with cancer from healthy persons, as well as to differentiate between clinical stages of the cancer.